The Prevalence and Factor Affecting Acne Vulgaris Among Nangarhar University Students - Imamzai, Iqbal Shah; Sajjad, Samiullah (International Journal For Research In Health Sciences And Nursing, 2020)
Background: Acne can cause severe psychological problems, undermining self-assurance and self-esteem at a vulnerable time in life. Acne is one of the most common skin diseases. A significant number of patients either continue to experience acne or develop new-onset acne after the teenaged years. Objective: To study the prevalence of acne in Nangarhar university students and to investigate risk factors for acne in these subjects. Methods: We have randomly selected university students above 18 years of age, males and females. A questionnaire was designed and distributed to the students and the results were analyzed by SPSS. This study was carried out in Nangarhar University at Medical, Computer Science and Education faculties from 15 SEP 2019 to 15 MAR 2020. Results: There was a high prevalence of acne on the face, back and chest, with high rates of dissatisfaction in males and females. High proportion of males and females had oily skin and males had significantly higher proportion of oily skin compared to females. High proportion of subjects had family history of acne. Facial nature (dry, oily or combined), stress, family history of acne and using corticosteroids were significantly associated with higher incidence of acne. Our subjects had 1.8 times risk of developing acne because of facial nature, had 1.7 times of risk of developing acne if they were under stress compared to those who were stress-free, and had 3.5 times risk of developing acne if they come from a family with history of acne compared to those with no family history of acne. Subjects who used corticosteroids had 2.5 risk of developing acne compared to those who did not use corticosteroids. Conclusion: The students showed high prevalence of acne and facial nature, stress, family history of acne and use of corticosteroids were major risks for acne in these subjects.